2020
DOI: 10.3892/or.2020.7660
|View full text |Cite|
|
Sign up to set email alerts
|

Lapatinib‑induced inhibition of ovarian function is counteracted by the STAT3 pathway both in vivo and in vitro

Abstract: The present study was designed to ascertain whether lapatinib, a tyrosine kinase inhibitor of epidermal growth factor receptor (EGFR), affects ovarian reserve and fertility potential in a mouse model. Female C57BL/6 mice were treated with either vehicle or lapatinib (100 or 200 mg/kg/day orally) for 4 weeks, after which body weight, vaginal smears, follicle numbers, serum anti-Müllerian hormone (AMH) levels and mating outcomes were analyzed to assess the ovarian reserve and reproductive function. Slices from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Furthermore, in vitro culture of bovine ( da Rosa et al 2017 ) and porcine ( Nagyova 2012 ) oocyte–cumulus complexes indicated that the EGFR inhibitor AG1478 and lapatinib inhibited oocyte maturation and reduced expression of cumulus expansion-associated transcripts, respectively. Based on these findings, one would anticipate that EGFR inhibitors would have an adverse effect on fertility; however, a recent preclinical study where female mice were treated with either vehicle or lapatinib (100 or 200 mg/kg/day orally) for 4 weeks found no significant differences in ovarian morphology, total follicle numbers, anti-Mullerian hormone (AMH) levels, oestrous cyclicity, or mating outcomes in the three groups of mice ( Liao et al 2020 ). Further Western blotting and immunohistochemical investigation of the EGFR and its main downstream signalling pathways in isolated ovary cultures showed increased phosphorylation of STAT3 in the lapatinib-treated groups compared to the vehicle group, and it was hypothesised the lack of effect of lapatinib on ovarian function may be due to a compensatory effect of STAT3 signalling pathway activation.…”
Section: Egfr/her Inhibitorsmentioning
confidence: 99%
“…Furthermore, in vitro culture of bovine ( da Rosa et al 2017 ) and porcine ( Nagyova 2012 ) oocyte–cumulus complexes indicated that the EGFR inhibitor AG1478 and lapatinib inhibited oocyte maturation and reduced expression of cumulus expansion-associated transcripts, respectively. Based on these findings, one would anticipate that EGFR inhibitors would have an adverse effect on fertility; however, a recent preclinical study where female mice were treated with either vehicle or lapatinib (100 or 200 mg/kg/day orally) for 4 weeks found no significant differences in ovarian morphology, total follicle numbers, anti-Mullerian hormone (AMH) levels, oestrous cyclicity, or mating outcomes in the three groups of mice ( Liao et al 2020 ). Further Western blotting and immunohistochemical investigation of the EGFR and its main downstream signalling pathways in isolated ovary cultures showed increased phosphorylation of STAT3 in the lapatinib-treated groups compared to the vehicle group, and it was hypothesised the lack of effect of lapatinib on ovarian function may be due to a compensatory effect of STAT3 signalling pathway activation.…”
Section: Egfr/her Inhibitorsmentioning
confidence: 99%
“…Interestingly, the ovary may be able to overcome KIinduced damage via compensatory upregulation of alternative cell cycle signaling pathways. Upregulation of the signal transducer and activator of transcription 3 (STAT3) pathway in mice has been found to counteract the inhibition of EGFR caused by lapatinib, for example [(Liao et al, 2020)]. This may explain the overall neutral effect on corpora lutea seen in animal models exposed to KI therapy [ (Catlin et al, 2019), (Zhang & Tian, 2020)].…”
Section: Ovarian Functionmentioning
confidence: 99%